Institutional Adaptation of Islamic Boarding Schools in Indonesia: Balancing Tradition and Modern Education - Muttaqin, Ahmad Ihwanul (JURNAL AL-TANZIM, 2025)
This study examines the institutional adaptation of Islamic boarding schools (pesantren) in Indonesia in response to social, cultural, and educational changes. The primary focus of this research is the dynamics of change in governance, curriculum, and organisational practices in Islamic boarding schools. This research uses a qualitative design with a phenomenological-sociological approach. Data were obtained through in-depth interviews with kiai, administrators, teachers, students, and alumni, as well as institutional archival documentation and direct observation. Data analysis was conducted using the adaptive strategy framework, institutional change theory, and Philip A. Woods' four elements of adaptation: amplification, instrumental artifacts, freedom as a capability, and resource mobilisation. The results show that amplification is rooted in reforms that affirm the core values of Islamic boarding schools, while instrumental artifacts are evident in formal education and alumni collaboration. Freedom is reflected in governance that allows for limited space for innovation, and resource mobilisation combines symbolic and material capital to support change. Islamic boarding school adaptation is selective, employing a strategy of "resisting while following," which maintains cultural authenticity while competing in modern education. This research provides implications that Islamic boarding schools are selective in maintaining cultural authenticity and competitiveness in the modern education landscape.